Time series modeling for the Davao River water quality parameters - Magabili, Elmer Fuentes (2005)
Time series exponential smoothing model was developed for every parameter of all the eight stations of the Davao River water quality parameters namely biochemical oxygen demand (BOD), dissolved oxygen (DO), pH, temperature, total suspended solids (TSS), and total dissolved solids (TDS), using the quarterly data obtained from the Environmental Management Bureau (EMB) of Region XI. The model estimates the values or one-period ahead forecasts of the water quality parameters of Davao River for eight stations. Using the model obtained, the one-period ahead forecasts was done in each of the water quality class II and stations 6 to 8 are classified to be public water supply class I. with the model obtained, forecast for the next quarter?s possible values of each parameter in every station was done and were still considered Class I for stations 6 to 8 and class II for stations 1 to 5. The model developed maybe used as guide by the EMB of Region XI in making regulations and plans of action to preserve the water quality of all stations from future and potential contaminations